PENGIMPLEMENTASIAN TEKNOLOGI PROGRAMMABLE LOGIC DEVICE (PLD) SEBAGAI BINER CODE DECIMAL (BCD) UNTUK SCANNING KEYPAD - Muhammad Irmansyah (Elektron : Jurnal Ilmiah, 2013)
Industrial of electronics developed in many fields in the middle of 1990s. Base on this situation, the manufacturer produce the product by increased the function, display, low cost, low power consumption and small size. This kind of product must be supported by complex system, small number of integrated circuit and tiny printed circuit board (PCB). Many integrated technologies such as submicron semiconductor, PCB technology, and the using of PCB surface maximal. The market situation push the producer used modern technology in design and testing for example Programmable Logic Device (PLD). It is the integrated circuit using digital logic which can be changed this function by programming and can be used to industrial application. Programmable Logic Device (PLD) technology can be used to many logical programming by using only one IC. The application of this technology can be found in IC 22V10 with 24 pins. This IC can be applied to replace the function of IC 74299 as encoder decimal to biner to scanning keypad.